Memahami Chatgpt dan Potensi Dampaknya pada Pendidikan: Perspektif Filsafat - Viki Love Reformasianto; Niswatul Faizah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research aims to investigate the essence of ChatGPT from a philosophical perspective, evaluate its positive and negative impacts, and provide practical guidance for users in various contexts. This research was conducted using the literature study method, specifically narrative review, as the main approach. It is concluded that from a philosophical perspective, ChatGPT raises ontological questions regarding the existence of entities without consciousness or physical bodies, and challenges traditional understandings of agents that meaningfully interact with humans. In terms of epistemology, the validity of the knowledge generated by ChatGPT depends on the quality of the training data, and users should be critical in accepting the information provided. Axiologically, values such as fairness, transparency, and responsibility should be considered in the use of ChatGPT. While it can increase efficiency in data analysis, writing, and scientific research, over-reliance on this technology can hinder the development of critical thinking skills. However, if used wisely, ChatGPT can stimulate discussion, ask challenging questions, and offer new perspectives, thus enriching the critical thinking process. Educational institutions and individual users need to develop guidelines for the use of ChatGPT to ensure this technology enriches, not replaces, the critical thinking process.